Pengaruh cognitive benefits, social integrative benefits, personal integrative benefits, dan hedonic benefits terhadap customer engagement smartphone xiaomi - Rahmad Dani; Arief Maulana (Universitas Negeri Padang, 2020)
This study analyzes (1) the effect of cognitive benefits on customer engagement (2) the effect of social integrative benefits on customer engagement (3) the effect of personal integrative benefits on customer engagement (4) the effect of hedonic benefits on customer engagement. The population in this study was societies used smartphone xiaomi in Padang city, the sample in this research 100 respondents, the taking technique was accidental sampling. The research was analyzed using the multiple regression analysis approach using SPPS software version 16. The results of the research were: (1) cognitive benefits has a significant effect on customer engagement (2) social integrative benefits has a significant effect on customer engagement (3) personal integrative benefits has an insignificant effect on customer engagement (4) hedonic benefits has a significant effect on customer engagement.